Diseño de un mecanismo técnico operativo para la aplicación de la metodología Aflateen para promover el ahorro y emprendimiento en los adolescentes y jóvenes de la comunidad lucha de los pobres del Centro Comunitario Nº 5 a través de la Cooperativa de Ahorro y Crédito Mushuk Yuyai - Acosta Rodríguez, Rosa Isabel (2014)
We have designed a technical operational mechanism for the implementation of the Aflateen methodology through the Cooperative “Mushuk Yuyai”, to provide social and financial education to young people of the “Lucha de los Pobres” neighborhood, located in the South of Quito. This project is based on the limited involvement the financial institutions have for to development of social activities, which is why it was necessary to link the participation of the Cooperative Mushuk Yuyai that will provide training on savings and entrepreneurship, being the first institution to use Aflateen Methodology for the benefit of a community. You can know the problems, causes and constraints the people of the “Lucha de los Pobres” neighborhood are facing, then the research problem is established to improve the living conditions of the population by applying the Aflateen methodology.